Characterization of fetal arrhythmias by means of fetal magnetocardiography in three cases of difficult ultrasonographic imaging. - Comani, S; Liberati, M; Mantini, D; Gabriele, E; Brisinda, D; Di Luzio, S; Fenici, R; Romani, G (2004)
Characterization of ultrasound detected fetal arrhythmias is generally performed by means of M-mode and pulsed Doppler echocardiography (fECHO), sonographic techniques that allow only indirect and approximate reconstruction of the true electrophysiological events that occur in the fetal heart. Several studies demonstrated the ability of fetal magnetocardiography (fMCG) to identify fetal arrhythmias. We report on three women, studied after the 32nd gestational week, who were referred for fMCG because of unsatisfying fetal cardiac visualization with fECHO due to maternal obesity, fetus in constant dorsal position hiding the fetal heart, intrauterine growth retardation, and oligohydramnios. Minor pericardial effusion was present in the third patient and digoxin therapy was given. FMCG were recorded with a 77-channel MCG system working in a shielded room. Independent Component Analysis (FastICA algorithm) was used to reconstruct fetal signals. The good quality of the retrieved fetal signals allowed real-time detection of arrhythmias and their classification as supraventricular extrasystoles (SVE), with/without aberrant ventricular conduction and/or atrioventricular block. The time course of the fetal cardiac rhythm was reconstructed for the entire recording duration; hence, fetal heart rate variability could be studied in time and frequency. Since isolated extrasystoles may progress to more hazardous supraventricular tachycardias, the noninvasive antenatal characterization of, even transient, fetal arrhythmias and their monitoring during pregnancy can be of great clinical impact.